SUCCESS FACTORS IN LOGISTICS MANAGEMENT AND DURIAN SUPPLY CHAIN INTEGRATION OF THE EASTERN AGRICULTURAL COOPERATIVES - Pisitkasem, Phat (RMUTT Global Business and Economics Review, 2023)
The research study on Success Factors in Logistics Management and Durian Supply Chain Integration of the Eastern Agricultural Cooperatives is to investigate important logistics management activities that influence the success of farmers operating durian businesses in the Eastern Agricultural Cooperatives. As well as to investigate the supply chain coordination model that combines to promote durian farmers in the Eastern Agricultural Cooperatives. Farmers or those involved in the cultivation and distribution of durians in the Eastern Agricultural Cooperatives are key informants. The sample included ten people from Chanthaburi, Trat, and Rayong Province. Snowball testing In-depth interviews and structured interviews were used in this study. The information gathered is used for content analysis. The findings revealed that key informant general information it includes 7 to 20 years of work experience. The majority of the durian species operated will be Monthong varieties, followed by gibbons, Kanyao, Phuangmanee, and Buttons. The amount of durian planting area, if it is a grower, will be 40-200 rai, but if it is the total planting area of farmers who send durian to each product cooperative, will be 2,000-66,000 farm. Eastern durian produce will be available once a year from April to June, with some off-season at the start and end of the season. Logistics and Supply Chain Success Factors to Consider There are ten logistics tasks which must be completed: customer services, receiving customer orders, forecasting and demand management Inventory management, logistics, warehousing, and storage management are all aspects of inventory management. outside procurement reverse logistics Cargo handling equipment, packaging, and logistics communications The Eastern Agricultural Cooperatives' supply chain for the durian business Upstream businesses, government sectors, such as the Department of Plant Pathology, District Agriculture Officer, Provincial Agriculture Officer, Agricultural Research and Development Office, District 6, Department of Agriculture, Ministry of Agriculture and Cooperatives, and provincial governors, make up the consortium. Farmers and agrochemical companies are examples of private sectors. Workers in the durian garden Lhong, middlemen, and export companies selling abroad are examples of midstream businesses. Plant for the Processing of Frozen Lamb Durian. Providers of shipping and parcel services Customers for downstream businesses are mostly Chinese durians. Laos is a customer market for Japanese durian. Domestic traders from various regions of the country participate in modern trade, as do clients who purchase durians online.